INSTAGRAMMING INFLUENCE: UNRAVELLING THE POWER OF SOCIAL MEDIA IN BRAND MARKETING - Ishita Pareek, Dr. Bhargavi D Hemmige, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
In an era driven by digital interactions, social media's function in brand marketing has become increasingly important. The purpose of this research paper is to investigate the multidimensional influence of social media platforms on modern marketing techniques and brand promotion. The paper analyses the symbiotic relationship between brands and social media, revealing the processes by which these platforms contribute to brand awareness, consumer engagement, and overall market success, using a comprehensive analysis of relevant literature and case studies. The study goes into the wide range of social media outlets, examining how each platform brings its own set of opportunities and problems for brand promotion. It also investigates the changing trends and technology that will shape the future landscape of social media marketing. The study deconstructs the unique techniques businesses utilise to maximise their reach and resonance in the digital environment, from influencer collaborations to user-generated content. Furthermore, the article investigates the role of social media analytics and metrics in determining campaign efficacy and ROI. This study attempts to distil best practices and give helpful insights for marketers navigating the dynamic environment of social media by objectively assessing successful and failed brand promotion strategies. Finally, this research paper adds to a better understanding of the role social media plays in defining modern brand marketing tactics, equipping marketers with the knowledge they need to fully use these powerful digital platforms.